Comparative Analysis Based on New Competitiveness Index - Savić, Nebojša (Panoeconomicus, 2012)
The current economic crisis points out to an even greater need to improve competitiveness. Since 2005, numerous developing countries have succeeded in increasing their competitiveness scores and decreasing the difference relative to advanced countries. The countries of Central and South Eastern Europe, to which Serbia belongs, have recorded an increase in their score by 0.3 on average, whereby the region of South Eastern Europe has achieved poorer results. During the period 2005-2011, Serbia recorded an increase in its score by 0.5, from 3.38 to 3.88. In 2011, Serbia was ranked 95th among 142 countries, with the score of 3.88. This is a decline relative to 2008 and 2005, when Serbia was ranked 85th with the scores of 3.38 and 3.90 respectively. However, this increase was not sufficient to improve Serbia’s ranking, which shows that other countries were more successful. This faces Serbia with the task to strengthen its efforts towards improving competitiveness.Key words: Competitiveness, Porter’s diamond, Productivity, Serbia.JEL: F23, O57.